2002
DOI: 10.1001/archneur.59.2.243
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Corpus Callosum Atrophy in Alzheimer Disease

Abstract: Measurement of corpus callosum size allows in vivo mapping of neocortical neurodegeneration in AD over a wide range of clinical dementia severities and may be used as a surrogate marker for evaluation of drug efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
112
1
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(138 citation statements)
references
References 25 publications
22
112
1
3
Order By: Relevance
“…Our findings are consistent with previous reports of regionally specific posterior callosal atrophy in mild AD [23,38]. Studies showing more pervasive callosal atrophy have typically involved AD patients with moderate or severe dementia [18,20,21,23,27,34,35]. For example, one study [23] found atrophy in all callosal subregions in their total AD sample; however, when just the mild AD subset from the AD group was analyzed, only the posterior mid-body, isthmus, and splenium showed significant reduction relative to controls.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our findings are consistent with previous reports of regionally specific posterior callosal atrophy in mild AD [23,38]. Studies showing more pervasive callosal atrophy have typically involved AD patients with moderate or severe dementia [18,20,21,23,27,34,35]. For example, one study [23] found atrophy in all callosal subregions in their total AD sample; however, when just the mild AD subset from the AD group was analyzed, only the posterior mid-body, isthmus, and splenium showed significant reduction relative to controls.…”
Section: Discussionsupporting
confidence: 91%
“…Also, longitudinal research involving the early AD, MCI, and CC groups will help determine the onset and progression of these callosal changes. One study [34] found that the annual rate of atrophy of the total corpus callosum, rostrum, anterior truncus, and splenium of AD patients was 7.7%, 12.1%, 10.3% and 7.3%, respectively. An additional important future direction will be the application of computational anatomic approaches to model shape changes in the early preclinical stages of AD and in those at risk for AD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relation of the atrophic change to the pathologic involvement, however, needs to be demonstrated with postmortem studies. 87 Automated or semiautomated MR volumetry techniques that are less labor-intensive than tracing specific regions of interest are being used to track the structural changes that take place within the brain during the progression of AD. One of the most promising techniques used for this purpose is the brain boundary shift integral (BBSI) developed by Fox and Freeborough.…”
Section: Both Antemortem and Postmortem Mr Studies Indicate That Mr-bmentioning
confidence: 99%
“…One of the proposed targets is the corpus callosum (CC), a large white matter tract that includes the neural pathway starting at the nucleus basalis of Meynert, and connects the majority of frontal, parietal, and occipital cortical areas to corresponding regions in the contralateral hemisphere. CC size changes and atrophy occur in AD patients and correlate with progression of dementia severity 9, 10, 11. This, coupled with the fact that stem cells migrate through large white matter tracts,12, 13, 14 makes the CC a potentially effective target.…”
Section: Introductionmentioning
confidence: 99%